Case Study: Foreign Workers in Malaysia - Al Masud, Sheikh Mohammad Maniruzzaman; Rohana, Hamzah; Hasan, Ahmad (Transnational Press London, 2020)
Malaysia has become a popular destination for many foreign workers since getting independence in 1957, owing to its rapidly growing economy and industrialisation. Most of the migrant workers in Malaysia are low-skilled or uneducated, and public debate is going on their outcome, whether it is substantial or not. The purpose of this study is to manifest the role and contribution of imported labour to the Malaysian economy. Evidence is collected from secondary sources- journal article, relevant books, and online databases. The review finds that the impact of migrant labour on Malaysian growth has not been studied holistically and sufficiently. Existing evidence shows that although it is somewhat positive, the public attitude is most adverse to illegal and irregular migrants. Therefore, more empirical research is required to determine the role of imported temporary workers on the economy of Malaysia, for its ongoing vision- to become a high-income nation.